1989
DOI: 10.1007/bf00273560
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of Dextran 40: effect on cerebral blood flow and metabolic rates in acute head trauma

Abstract: A controlled double-blind evaluation of the effects of Dextran 40 at different concentrations on cerebral blood flow (CBF), cerebral oxygen consumption (CMRO2) and cerebral lactate production (CMRLact) was carried out. We studied 40 patients in coma due to recent head injury. Concentrations of Dextran solution were not significantly related to variations in CBF and metabolic rate over the period of infusion. The lack of effect of the Dextran infusion may be explained by the absence of global brain ischemia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Nevertheless, the results of several studies in animals and humans have demonstrated a major decline in cerebral O 2 consumption after TBI. 3,18,31,38 Moreover, in the present study the increases observed in brain tissue PCO 2 were regularly accompanied by a drop in brain tissue PO 2 . Given that decarboxylation reactions (for example, decarboxylation of pyruvate, isocitrate, and ␣-ketoglutarate before and during the tricarboxylic acid cycle) as part of oxidative glucose metabolism and ATP generation are the main metabolic source of cerebral CO 2 production, and because these reactions are inhibited in the absence of sufficient O 2 by increased concentrations of the reduced form of nicotinamide adenine dinucleotide, a decrease in CO 2 production, instead of a rise, would be expected.…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, the results of several studies in animals and humans have demonstrated a major decline in cerebral O 2 consumption after TBI. 3,18,31,38 Moreover, in the present study the increases observed in brain tissue PCO 2 were regularly accompanied by a drop in brain tissue PO 2 . Given that decarboxylation reactions (for example, decarboxylation of pyruvate, isocitrate, and ␣-ketoglutarate before and during the tricarboxylic acid cycle) as part of oxidative glucose metabolism and ATP generation are the main metabolic source of cerebral CO 2 production, and because these reactions are inhibited in the absence of sufficient O 2 by increased concentrations of the reduced form of nicotinamide adenine dinucleotide, a decrease in CO 2 production, instead of a rise, would be expected.…”
Section: Discussionsupporting
confidence: 67%
“…This observation has been attributed to the early metabolic suppression rather the global ischemia which predominates in the early phase of head injury and thus could not be benefitted by the use of dextran solution. [23] Similarly, the normovolemic hemodilution in both adults and pediatric brain injury models, were found to be ineffective as these tend to cause hyperemia and increased transfer of water content across BBB that produced further cell swelling. [24] The popular ‘The Saline versus Albumin Fluid Evaluation (SAFE) study’ has been shown to cause increase in mortality among TBI patients who were treated with albumin.…”
Section: Effects On Cerebral Physiologymentioning
confidence: 99%